KINERJA BISNIS USAHA BAHAN MAKANAN SEGAR ONLINE DI BANDAR LAMPUNG - Sari, I.Rani Mellya; Rahmalia, Dian; Kasymir, Eka; Indah, Iva Mutiara; Nismara, Anindya Putri (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
Human civilization is entering a disruptive era of technology indicated by behaviour changes and the discovery of new patterns, one of which is digital transformation. It was further triggered by the global COVID-19 pandemic. The right digital marketing model contributes to a massive digital technology-based market transformation to increase the welfare of agricultural business actors. The research focuses on business actors that utilize digital technology in the category of fresh food products. The aims of this research are: 1). Analyzing the effectiveness of digital marketing, and 2). Analyzing business performance. The research using basic case study method. The research location was chosen purposively, namely three business actors, by utilizing digital innovation.The results shows that the business performance of selling fresh food online in Bandar Lampung is divided into two aspects, namely production performance and management performance. Production performance is based on productivity, quality, capacity, process, delivery speed, flexibility, and processing speed to layout. Meanwhile, management performance is based on guidelines regarding good food production methods for home industries, from 13 assessment indicators, it was found that business A was in the category of minor deviation, business actor B and C was in the category of major deviation. Keywords: Digital Transformation, Digital Marketing Effectiveness, Groceries